Edutaiment Dalam Perkembangan Nilai Nilai Moral Dan Agama Anak - Husnul Bahri; Fitriani Fitriani (At-Ta'lim : Media Informasi Pendidikan Islam, 2019)
Abstract: Edutainment in Development Moral Value and Religious Value. Moral and religious values education is a conscious effort that is carried out by humans (adults) planned to provide opportunities for students (children, future generations) to instill values into the Godhead, aesthetic and ethical values, good and bad values, right and wrong, regarding actions, attitudes and obligations, noble character, noble mind and character to achieve maturity and responsibility, or the rules and religious values held by the local community. The strategy for developing religious values is through routine activity programs, integrated programs, and special activity programs. While the strategies and techniques of moral development in early childhood are: through training strategies and habituation, play activity strategies. Learning strategies. Edutainment as a fun learning approach in developing moral and religious values in Kindergarten can be done in several ways, namely: singing, playing, creating a pleasant, conducive and comfortable learning atmosphere, conditioning the child's psychological readiness to start learning, readiness conditioning physically students for learning, conditioning student learning interests, enthusiastic conditioning of students in the middle of class, final conditioning of learning hours.Abstrak: Edutaiment Dalam Perkembangan Nilai Nilai Moral Dan Agama Anak. Pendidikan nilai moral dan agama adalah suatu usaha sadar yang dilakukan manusia (orang dewasa) yang terencana untuk memberikan kesempatan kepada peserta didik (anak, generasi penerus) menanamkan nilai-nilai ke Tuhanan, nilai-nilai estetik dan etik, nilai baik dan buruk, benar dan salah, mengenai perbuatan, sikap dan kewajiban, akhlak mulia, budi pekerti luhur agar mencapai kedewasaannnya dan bertanggung jawab, atau aturan dan nilai-nilai agama yang dipegang masyarakat setempat. Strategi pengembangan nilai-nilai keagamaan yaitu melalui program kegiatan rutinitas, program terintegrasi, dan program kegiatan khusus. Sedangkan strategi dan tehnik pengembangan moral pada anak usia dini yaitu : melalui strategi latihan dan pembiasaan, strategi aktivitas bermain. Strategi pembelajaran. Edutainment sebagai suatu pendekatan pembelajaran yang menyenangkan dalam pengembangan nilai-nilai moral dan agama dapat dilakukan dengan beberapa cara yaitu : bernyanyi, bermain, menciptakan suasana pembelajaran yang menyenangkan, kondusif dan nyaman, mengkondisikan kesiapan psikis anak memulai pembelajaran, pengkondisian kesiapan pisik siswa untuk belajar, pengkondisian minat belajar siswa, pengkondisian antusias siswa ditengah jam pelajaran, pengkondisian akhir jam pembelajaran.